MENINGKATKAN KEMAMPUAN MENARI TARI BALANSE MADAM MELALUI METODE SAS UNTUK ANAK TUNARUNGU (Single Subject Research Kelas II SMP di SLB Bundo Kanduang Padang) - Yuli Afmi Ropitasari (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstrack: This study aims to test the effectiveness of the use of SAS methods in studyng dancing skills for children of dance of balanse madam in SLB Bundo Kanduang Padang. This research was using Single Subject Research approach wit AB design. Subjects were a deaf children in class II SMPLB. To measure the research variables, the percentage of the techniques applied. Based on the results of data analysis, it was found that the use of SAS method effective to improve dancing skills of balanse madam in class II SMP SLB Bundo Kanduang Padang. Kata-kata kunci: Metode SAS; Menari; Tari Balanse Madam; Tunarungu